Inoculated host range and effect of host on morphology and size of Macroconidia produced by Claviceps africana and Claviceps sordhi - Muthusubramanian, V.; Bandyopadhyay, Ranajit; Tooley, P.; Rajaram Reddy, D. (Wiley, 2005)
Twenty graminaceous plant species were evaluated for their susceptibility to the two sorghum ergot pathogens Claviceps sorghi and Claviceps africana. Five speciesviz.,Sorghum arundinaceum, Sorghum halepense, Sorghum versicolor, Sorghum virgatum and Pennisetumglaucum were found to become infected by both pathogens via inoculation with 106conidia/ml. Species which did not become infected under these conditions included Pennisetum pedicellatum, Zea mays, and species ofPanicum, Brachiaria, Cenchrus, Andropogon,Dichan-thium,Chrysopogon,Iseilema,BothriochloaandChloris. Honeydew secretions were observed from infected flowers of susceptible plant species. There was marked variation in size of macroconidia of bothC. sorghi and C. africanaon different hosts on which the pathogenswere able to establish symptoms. Dimorphism was observed for macroconidia produced on P. glaucum, aselliptical and spindle shaped macroconidia were observed. Based on inoculation under greenhouse conditions, we conclude that C. sorghi and C. Africana may have similar host ranges.